Optimizing machine-learning-based NILM: A comparative analysis of wavelet feature extraction for high-accuracy appliance classification - Nathan Morris; James Gopsill; Maria Valero; Sam Williamson; Ben Hicks (Energy and Buildings, 2026)

E-selectin and transferrin receptor functionalized synthetic miRNA nanoshuttles with therapeutic potential in stroke - Valérie Petegnief; Maria Kannavou; Valeria Peli; Carles Justicia; Foteini Gkartziou; Alicia Aliena-Valero; Leire Pedrosa; Juan B. Salom; Dorian Tace; Anna M. Planas; Sophia G. Antimisiaris; Lorenza Lazzari (Drug Delivery and Translational Research, 2026)
Current acute ischemic stroke treatment is limited to reperfusion therapies within the first hours after the onset, underscoring the urgent need for novel therapeutic strategies to mitigate the progression of the brain lesion. Here, we describe the development of bio-inspired synthetic nanoshuttles—lipid nanoparticles (LNPs)—designed to deliver miRNAs and target post-stroke inflammation, a key contributor to secondary brain damage. miRNAs isolated from human induced pluripotent stem cells (hiPSCs) were encapsulated into LNPs prepared by a microfluidic technique. We produced small sized, uniform nanoparticles with high miRNA encapsulation efficiency. LNPs were functionalized with anti-transferrin receptor (TfR) and anti-E-selectin antibodies to target the inflamed cerebral vasculature. We assayed LNPs’ effect in a model of vascular inflammation in vitro and in vivo following brain ischemia/reperfusion in mice. In cultured human brain endothelial cells, empty LNPs, dual-targeted empty LNPs, and dual-targeted LNP encapsulating miRNAs (DT-LNP) reduced lipopolysaccharide-induced interleukin-6 production, indicating a modulatory effect of the lipid carrier under our experimental conditions. Mice received, via i.v., either empty LNPs (control) or two different doses of DT-LNPs at reperfusion following brain ischemia. The low dose of DT-LNPs reduced infarct volume and tended to improve the neurological deficit, and to downregulate the expression of IL-1β and E-selectin mRNAs, whereas the high dose did not. Altogether, these findings provide proof-of-concept that TfR-E-selectin-targeted LNPs encapsulating hiPSC-derived miRNAs represent a promising therapeutic approach for stroke.

Cortical volumetry and longitudinal cognitive changes in Parkinson’s disease: insights from the COPPADIS cohort - Tania Álvarez-Avellón; Carmen Solares; Juan Álvarez-Carriles; Pablo Franco-Rosado; Patricia Diaz-Galvan; Diego Santos-García; Pablo Mir; Manuel Menéndez-González; Astrid Adarmes Daniela; Almeria Marta; Maria Gema Alonso Losada; Araceli Alonso Cánovas; et al. (Brain Imaging and Behavior, 2025)
Cognitive decline is a major non-motor symptom in Parkinson’s disease (PD), often linked to brain atrophy. This study examines the relationship between cortical atrophy and age groups in predicting cognitive decline in PD over five years. 188 PD patients from the COPPADIS cohort were stratified by age: young (30–55 years, N = 47), middle-aged (56–65 years, N = 59), and older adults (66–75 years, N = 82). Baseline cortical volume was assessed using T1-weighted MRI, and cognitive decline was evaluated using the annual rate of change of the Parkinson’s Disease-Cognitive Rating Scale (PD-CRS). Parametric or non-parametric tests were applied to evaluate group differences. Main analyses consist of several multiple regression analyses to examine associations between baseline brain atrophy and cognitive decline by age group. Older adults exhibited significantly greater cognitive decline in comparison to the younger age groups in the three compose scores of the PDCRS -Fronto-subcortical (H(2) = 41.08, p < 0.001), Posterior Cortical (H(2) = 22.03, p < 0.001), and Total(H(2) = 41.13, p < 0.001). Higher educational level has a significant positive effect on older adults, specifically for working memory performance, delayed verbal memory and the fronto-subcortical composed score. Multiple regression models underscored the predictive value of the bilateral hippocampus, bilateral medial orbitofrontal cortex, right precuneus, and right isthmus cingulate gyrus, together with being an older adult or having a higher education. MRI measures, age, and education predict cognitive decline in PD. Longitudinal assessments are essential for refining atrophy-cognition correlations and optimizing patient stratification.

In-depth analysis of natural organic matter fractions in drinking water treatment performance: Fate and role of humic substances in trihalomethanes formation potential - Meritxell Valenti-Quiroga; Alba Cabrera-Codony; Pere Emiliano; Fernando Valero; Hèctor Monclús; Maria J. Martin (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Evaluation of the organoleptic perception of a new saffron (Crocus sativus L.) powder as a flavoring substitute for saffron stigmas in culinary applications - Elena Álvarez; Daniel González-Hedström; María Inés Morán-Valero; Rosa Maria SanJuan; Verónica Trapero; Marina Díez-Municio (International Journal of Gastronomy and Food Science, 2024)

Correlation of hepatitis E and rat hepatitis E viruses urban wastewater monitoring and clinical cases - Maria Casares-Jimenez; Transito Garcia-Garcia; José M. Suárez-Cárdenas; Ana B. Perez-Jimenez; María A. Martín; Javier Caballero-Gómez; Carmen Michán; Diana Corona-Mata; María A. Risalde; Ignacio Perez-Valero; Rafael Guerra; Ignacio Garcia-Bocanegra; et al. (Science of The Total Environment, 2024)

Increased serum ferritin and interleukin-18 levels in children with dengue - Nereida Valero; Jesus Mosquera; Mariana Torres; Anyelo Duran; Maria Velastegui; Javier Reyes; Miriam Fernandez; Gerardo Fernandez; Teresa Veliz (Brazilian Journal of Microbiology, 2019)

Increase of Candida antarctica lipase B production under PGK promoter in Pichia pastoris: effect of multicopies - Julia Macedo Robert; Maritza Ocampo Betancur; Antonio Carlos Oliveira Machado; Andrelisse Arruda; Viviane Castelo Branco Reis; Rodrigo Volcan Almeida; Fernando Araripe Gonçalves Torres; Pau Ferrer Alegre; Francisco Valero; Denise Maria Guimarães Freire (Brazilian Journal of Microbiology, 2019)

Silencing of P2X7R by RNA interference in the hippocampus can attenuate morphological and behavioral impact of pilocarpine-induced epilepsy - Rebeca Padrão Amorim; Michelle Gasparetti Leão Araújo; Jorge Valero; Iscia Lopes-Cendes; Vinicius Davila Bitencourt Pascoal; João Oliveira Malva; Maria José da Silva Fernandes (Purinergic Signalling, 2017)

Comparison of the mitochondrial genomes of the Old and New World strains of the legume pod borer, Maruca vitrata (Lepidoptera: Crambidae) - Tolulope A. Agunbiade; Brad S. Coates; Weilin Sun; Mu-Rou Tsai; Maria Carmen Valero; Manuele Tamò; Barry R. Pittendrigh (International Journal of Tropical Insect Science, 2017)
Maruca vitrata (Fabricius, 1787) is a cryptic pantropical species of Lepidoptera that are comprised of two unique strains that inhabit the American continents (New World strain) and regions spanning from Africa through to Southeast Asia and Northern Australia (Old World strain). In this study, we de novo assembled the complete mitochondrial genome sequence of the New World legume pod borer, M. vitrata , from shotgun sequence data generated on an Illumina HiSeq 2000. Phylogenomic comparisons were made with other previously published mitochondrial genome sequences from crambid moths, including the Old World strain of M . vitrata . The 15,385 bp M. vitrata (New World) sequence has an 80.7% A+T content and encodes the 13 protein-coding, 2 ribosomal RNA and 22 transfer RNA genes in the typical orientation and arrangement of lepidopteran mitochondrial DNAs. Mitochondrial genome-wide comparison between the New and Old World strains of M. vitrata detected 476 polymorphic sites (4.23% nucleotide divergence) with an excess of synonymous substitution as a result of purifying selection. Furthermore, this level of sequence variation suggests that these strains diverged from ~1.83 to 2.12 million years ago, assuming a linear rate of short-term substitution. The de novo assemblies of mitochondrial genomes from next-generation sequencing (NGS) reads provide readily available data for similar comparative studies.

The L egionella pneumophila kai operon is implicated in stress response and confers fitness in competitive environments - Maria Loza‐Correa; Tobias Sahr; Monica Rolando; Craig Daniels; Pierre Petit; Tania Skarina; Laura Gomez Valero; Delphine Dervins‐Ravault; Nadine Honoré; Aleksey Savchenko; Carmen Buchrieser (Environmental Microbiology, 2014)
Summary L egionella pneumophila uses aquatic protozoa as replication niche and protection from harsh environments. Although L . pneumophila is not known to have a circadian clock, it encodes homologues of the KaiBC proteins of C yanobacteria that regulate circadian gene expression. We show that L . pneumophila kaiB , kaiC and the downstream gene lpp1114 , are transcribed as a unit under the control of the stress sigma factor RpoS . KaiC and KaiB of L . pneumophila do not interact as evidenced by yeast and bacterial two‐hybrid analyses. Fusion of the C ‐terminal residues of cyanobacterial KaiB to L egionella KaiB restores their interaction. In contrast, KaiC of L . pneumophila conserved autophosphorylation activity, but KaiB does not trigger the dephosphorylation of KaiC like in C yanobacteria . The crystal structure of L . pneumophila KaiB suggests that it is an oxidoreductase‐like protein with a typical thioredoxin fold. Indeed, mutant analyses revealed that the kai operon‐encoded proteins increase fitness of L . pneumophila in competitive environments, and confer higher resistance to oxidative and sodium stress. The phylogenetic analysis indicates that L . pneumophila KaiBC resemble S ynechosystis KaiC2B2 and not circadian KaiB1C1 . Thus, the L . pneumophila K ai proteins do not encode a circadian clock, but enhance stress resistance and adaption to changes in the environments.

Exploratory study on the influence of climatological parameters on Mycoplasma hyopneumoniae infection dynamics - Joaquim Segalés; Oliver Valero; Anna Espinal; Sergio López-Soria; Miquel Nofrarías; Maria Calsamiglia; Marina Sibila (International Journal of Biometeorology, 2012)

Climate changes and human activities recorded in the sediments of Lake Estanya (NE Spain) during the Medieval Warm Period and Little Ice Age - Mario Morellón; Blas Valero-Garcés; Penélope González-Sampériz; Teresa Vegas-Vilarrúbia; Esther Rubio; Maria Rieradevall; Antonio Delgado-Huertas; Pilar Mata; Óscar Romero; Daniel R. Engstrom; Manuel López-Vicente; Ana Navas; et al. (Journal of Paleolimnology, 2011)

Pharmacological and functional properties of TRPM8 channels in prostate tumor cells - Maria Valero; Cruz Morenilla-Palao; Carlos Belmonte; Felix Viana (Pflügers Archiv - European Journal of Physiology, 2011)

Dialysability of Magnesium and Calcium from Hospital Duplicate Meals: Influence Exerted by Other Elements - Carlos Velasco-Reynold; Miguel Navarro-Alarcon; Herminia Lopez-Ga de la Serrana; Vidal Perez-Valero; Ahmad Agil; Maria C. Lopez-Martinez (Biological Trace Element Research, 2010)